Estudio de los procesos productivos para incrementar la productividad en la microempresa construcciones metálicas EL ARCO. - Aimacaña Alomoto, Andrea Mishell (2018)
The present research project carried out a study at the productive processes due to the fact that there is no control in the daily production of the Microcompany Construcciones Metálicas el Arco. In order to achieve increasing productivity, through the development of a Production Master Plan (MPS). For which Material Requirements Planning (MRP) was previously carried out, which facilitates knowing the economic and raw material investment necessary for the production of the weekly lot. By means of the simple mobile average method, the generated sales on following three months were predicted, managing to meet the demand generated by customers and supplying the markets to maintain a balanced production and costs reduction. The times analysis and movements the average capacity of optimal production was established to avoid overwork, overtime and dead time.Through the percentage results that showed the graphs of the months of January to June of the sales values and lost versus production, it was possible to know that the production does not supply the demand, what gender the plant exceeds the average capacity of production in most months and in others production was radically reduced. With this research, control is maintained over the daily production and inventories levels, avoiding overloads of jobs loss of time due to the purchase of materials, unnecessary storage costs and raw materials. For this the MPS managed of the unproductive times that were generated on some days of the week and distributed equally, also detailed the investment and list of raw material needed to produce in the period of time established. With these tools, the quality of the finished product and the profitability of the plant are guaranteed, as well as the decision-making of the working, economic and social environment of the Microenterprise.